2008
DOI: 10.1007/s10592-008-9612-3
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of island populations to in situ genetic conservation

Abstract: Genetic variation is often lower within island populations, however islands may also harbor divergent genetic variation. The likelihood that insular populations are genetically diverse or divergent should be influenced by island size and isolation. We tested this assumption by comparing patterns of genetic variation across all major island song sparrow populations along the Pacific North American coast. Allelic richness was moderately lowered even on islands which are close to large, potential sources. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 62 publications
2
36
0
Order By: Relevance
“…Islands harbor almost 10 times as many endemic plant and vertebrate populations as mainland areas (Kier et al 2009), and might contain a large portion of the genetic variation of widespread species (Wilson et al 2009). However, humans have had negative impacts on island populations, primarily through the introduction of invasive species (Reaser et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Islands harbor almost 10 times as many endemic plant and vertebrate populations as mainland areas (Kier et al 2009), and might contain a large portion of the genetic variation of widespread species (Wilson et al 2009). However, humans have had negative impacts on island populations, primarily through the introduction of invasive species (Reaser et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In a comparable case, the Island Scrub-Jay (Aphelocoma insularis), long considered a morphologically distinguishable subspecies of the widespread Western Scrub-Jay (Aphelocoma californica), has recently been shown to be highly divergent from any other west ern Aphelocoma Wayne 2005, Delaney et al 2008). Although such work has been limited, studies on other taxa have generally shown significant divergence of island populations from mainland conspecifics and limited contact among populations on the different islands (Ramirez and Beck witt 1995, Landry et al 1999, Eggert et al 2004, Rubinoff and Powell 2004, Wilson et al 2009). In addition, many species present on the Chan nel Islands have reached there in very recent times, whether through natural means or through human trans port (Powell 1994, Calderwood et al 2002, Mahoney et al 2003, Chatzimanolis and Cate rino 2007a.…”
mentioning
confidence: 99%
“…Such large datasets currently exist within the context of conservation genetics that could be used to address issues as fundamental as inbreeding depression and other evolutionary related phenomena (e.g. Wilson et al 2009;Pärn et al 2009). …”
Section: Discussionmentioning
confidence: 99%